An Analysis of High School Students' Mathematical Representation Skills on Relations and Functions - Putri, Nathania Salsabila; Riyanti , Asifa Ajeng Dwi; Saputri , Hana Febri; Wahyuni , Reni; Ullah , Naqeeb (International Journal of Applied Learning and Research in Algebra, 2024)
This research was carried out with the aim of analyzing the abilities of high school level students in solving relationship and function problems. This research method is a qualitative method with descriptive research type. This research was carried out at one of Pekanbaru High School with subjects in classes X.1 and X.2 at YLPI Pekanbaru High School, with a total of 6 students. The data collection technique used in this research is a written test technique in the form of a description consisting of 2 questions. After the students have completed the questions, the results of the answers will be analyzed by the researcher as a percentage of the students' results and the researchers will conduct interviews with the students regarding the answers they made. Based on the research results, the percentage of the "Visual Representation" indicator was 79.16%, which is included in the high category. Then the indicator "Mathematical Equations or Expressions" was 66.66%, which was included in the high category. Finally, the "Words or Written Text" indicator is 50%, which is in the medium category. Furthermore, the percentage of questions for mathematical representation ability is 80% for question number 1, in the high category and 88.33% for question number 2, in the very high category. So a conclusion can be drawn from the score obtained by the students, namely 84.16%, which is included in the very high category. It is hoped that the results of this research will provide maximum guidance for teachers to develop students' abilities in mathematics, especially relation and function material. Keywords: Analysis of Student Abilities, Mathematical Representations, Relations and Functions